2017
DOI: 10.1111/gcb.13914
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forests are thermally buffered despite intensive selective logging

Abstract: Tropical rainforests are subject to extensive degradation by commercial selective logging. Despite pervasive changes to forest structure, selectively logged forests represent vital refugia for global biodiversity. The ability of these forests to buffer temperature-sensitive species from climate warming will be an important determinant of their future conservation value, although this topic remains largely unexplored.Thermal buffering potential is broadly determined by: (i) the difference between the "macroclim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 70 publications
(118 reference statements)
5
57
1
Order By: Relevance
“…As a result, we found that even though logging had a profound impact on the height and density of forest canopies (Figure 3; Hardwick et al, 2015;Pfeifer et al, 2016), only under intense logging pressure or following the conversion of forests to oil-palm plantations was microclimate strongly affected. This is broadly consistent with recent work showing that logged forests in the tropics tend to be largely thermally buffered and do not differ substantially in their microclimate to old-growth stands (Senior, Hill, Benedick, et al, 2017;Senior, Hill, González del Pliego, et al, 2017). Yet while previous studies have for the most part been limited to making dichotomous comparisons between logged and unlogged forests, using high-precision ALS data acquired across a landscape where land-use intensity was manipulated experimentally we were able to characterize the effects of forest degradation on microclimate in terms of quantitative changes in forest structure.…”
Section: Canopy Structure and Topography As Drivers Of Understorey supporting
confidence: 91%
“…As a result, we found that even though logging had a profound impact on the height and density of forest canopies (Figure 3; Hardwick et al, 2015;Pfeifer et al, 2016), only under intense logging pressure or following the conversion of forests to oil-palm plantations was microclimate strongly affected. This is broadly consistent with recent work showing that logged forests in the tropics tend to be largely thermally buffered and do not differ substantially in their microclimate to old-growth stands (Senior, Hill, Benedick, et al, 2017;Senior, Hill, González del Pliego, et al, 2017). Yet while previous studies have for the most part been limited to making dichotomous comparisons between logged and unlogged forests, using high-precision ALS data acquired across a landscape where land-use intensity was manipulated experimentally we were able to characterize the effects of forest degradation on microclimate in terms of quantitative changes in forest structure.…”
Section: Canopy Structure and Topography As Drivers Of Understorey supporting
confidence: 91%
“…Certainly, our findings suggest that, in the face of large‐scale habitat degradation in the tropics, logged forests with some degree of canopy will be important for the persistence of terrestrial leeches and other invertebrates. As such, our findings add to the growing body of work that supports the conservation value of selectively logged forest in human‐modified tropical landscapes (Deere et al., ; Edwards et al., ; Senior, Hill, Benedick & Edwards, ) .…”
Section: Discussionsupporting
confidence: 73%
“…Canopy structure and composition play a key role in regulating the offset of maximum summer temperatures. Forests thus provide highly heterogeneous thermal environments, with maximum temperature conditions that are often much cooler than suggested by available climate layers (Jucker et al, ; Scheffers et al, ; Senior, Hill, Benedick, & Edwards, ). The maximum temperature offsets reported here compare well with the general patterns observed in temperate regions across the globe and might even increase if the forest temperatures were to be measured closer to the forest ground surface (De Frenne et al, ).…”
Section: Discussionmentioning
confidence: 99%